Fibre Computer Enables More Accurate Recognition of Human Activity - Cheng, Qianyi; Li, Jianfeng; Zhang, Qichong (Nano-Micro Letters, 2025)
The advancement of fibre electronics is crucial for developing wearable smart textiles. However, traditional single-function fibres are typically limited to basic sensing and data collection capabilities, lacking effective computational and multimodal signal processing abilities, thus significantly restricting their potential in human activity recognition. Recently, Gupta et al. introduced an innovative single-fibre computer embedding eight microelectronic devices, integrating sensing, communication, and computation into a single fibre. Establishing a distributed cooperative fibre network substantially enhanced human activity recognition accuracy from 67% (single-fibre scenario) to 95%. This novel approach effectively addresses the limitations of conventional smart fibres, paving the way for multi-point sensing, edge-based inference, and real-time human–computer interactions in future intelligent textiles. Highlights: 1 Conventional microelectronics are scaled to the fibre level for information processing and storage in flexible, stretchable textiles. 2 Compared to single-fibre systems, multi-fibre computational architectures with coordinating modules exhibit higher reliability and more comprehensive functionalities.